(untitled) (Environment & Health, 2017)
Objective: We performed a comparative analysis of the morphological status of the pupils of the first forms in urban schools of Ukraine with their peers in Europe (Poland, France) for the long-term period. Materials and methods: Morphological indices of the physical development of the Ukrainian 7 year-old first-formers (as an example of Lviv city) in accordance with regional standard (1995-1996) and criteria of the evaluation of physical development of school age children (2013) were compared with the anthropometric parameters of the similar age groups of Polish (studies of 2000 and 2010) and French schoolchildren (2000) taken from literature data. Statistical analysis of the research results was carried out by the standard methods for biomedical research using the MS Excel program. Results: The study of the physical development of junior school-age children indicates a difference between the indices of 7-year-old boys and girls, residing in Ukraine, Poland and France. Body length and body weight of the schoolchildren of the first forms in the urban schools of Ukraine (1995-1996) was significantly lower than those of the children in Poland and France, surveyed in 2000. At the same time interval the Ukrainian schoolchildren had a broader chest: chest circumference of the boys was more by 1.91 cm, and the girls – more by 3.84 cm in comparison with the similar parameters of their Polish peers. In 2000 the body mass indices of the boys in Poland were more (p